2016
DOI: 10.1093/nar/gkw262
|View full text |Cite
|
Sign up to set email alerts
|

Is a fully wrapped SSB–DNA complex essential forEscherichia colisurvival?

Abstract: Escherichia coli single-stranded DNA binding protein (SSB) is an essential homotetramer that binds ssDNA and recruits multiple proteins to their sites of action during genomic maintenance. Each SSB subunit contains an N-terminal globular oligonucleotide/oligosaccharide binding fold (OB-fold) and an intrinsically disordered C-terminal domain. SSB binds ssDNA in multiple modes in vitro, including the fully wrapped (SSB)65 and (SSB)56 modes, in which ssDNA contacts all four OB-folds, and the highly cooperative (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 77 publications
2
20
0
Order By: Relevance
“…Both proteins display ionic strength-dependent transitions between ssDNA-binding modes that involve switches in the size of ssDNA occluded 20 . Furthermore, binding of either protein to ssDNA is non-cooperative at physiological ionic strength (200 mM) 18, 19, 2123 . However, several key features distinguish these functional homologs.…”
Section: Resultsmentioning
confidence: 99%
“…Both proteins display ionic strength-dependent transitions between ssDNA-binding modes that involve switches in the size of ssDNA occluded 20 . Furthermore, binding of either protein to ssDNA is non-cooperative at physiological ionic strength (200 mM) 18, 19, 2123 . However, several key features distinguish these functional homologs.…”
Section: Resultsmentioning
confidence: 99%
“…A single molecule investigation conducted under near-physiological buffer conditions, and where the generation of ssDNA is coupled to DNA replication on a fork substrate, has shown that the human mitochondrial SSB (HmSSB) binds primarily using a low site size binding mode, likely the (SSB)35 mode [99] . Using linked EcSSB subunits, Waldman et al investigated the effect of preventing the formation of a fully wrapped ssDNA-SSB tetramer on cell viability [72] . By covalently linking two SSB subunits, they generated EcSSB "dimers" in which each subunit contains two OB-domains.…”
Section: Cellular Roles Of Dna Binding Modesmentioning
confidence: 99%
“…SSB is a functional homolog of human RPA and binds ssDNA noncooperatively and with very tight affinity (in pM range) at 200 mM ionic strength (28,29,(37)(38)(39). We previously demonstrated that, like RPA, SSB binds tightly to ssDNA adjacent to a P/T junction and restricts PCNA to the upstream duplex region by physically blocking diffusion of the sliding clamp along the adjacent ssDNA (36).…”
Section: Rpa Regulates Monoubiquitination Of Pcna On and Off Dnamentioning
confidence: 99%